2019
DOI: 10.1016/s2213-2600(19)30251-6
|View full text |Cite
|
Sign up to set email alerts
|

Live-attenuated Mycobacterium tuberculosis vaccine MTBVAC versus BCG in adults and neonates: a randomised controlled, double-blind dose-escalation trial

Abstract: Background Infants are a key target population for new tuberculosis vaccines. We assessed the safety and immunogenicity of the live-attenuated Mycobacterium tuberculosis vaccine candidate MTBVAC in adults and infants in a region where transmission of tuberculosis is very high. Methods We did a randomised, double-blind, BCG-controlled, dose-escalation trial at the South African Tuberculosis Vaccine Initiative site near Cape Town, South Africa. Healthy adult community volunteers who were aged 18-50 years, had re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 41 publications
0
80
0
2
Order By: Relevance
“…The present work describes vaccination with a heat-killed (HK) version of the live attenuated M. tuberculosis vaccine MTBVAC (Arbues et al, 2013) both in mice and non-human primates (NHP). MTBVAC is the first and only live attenuated tuberculosis vaccine based on M. tuberculosis that has reached clinical stages of development, and it has shown an excellent safety profile both in adults and newborns, as well as stronger immunogenicity compared to BCG (Spertini et al, 2015;Tameris et al, 2019). Results in the present study demonstrate improved efficacy of MTBVAC HK when given by intranasal route to mice previously vaccinated with subcutaneous BCG.…”
Section: Introductionmentioning
confidence: 56%
“…The present work describes vaccination with a heat-killed (HK) version of the live attenuated M. tuberculosis vaccine MTBVAC (Arbues et al, 2013) both in mice and non-human primates (NHP). MTBVAC is the first and only live attenuated tuberculosis vaccine based on M. tuberculosis that has reached clinical stages of development, and it has shown an excellent safety profile both in adults and newborns, as well as stronger immunogenicity compared to BCG (Spertini et al, 2015;Tameris et al, 2019). Results in the present study demonstrate improved efficacy of MTBVAC HK when given by intranasal route to mice previously vaccinated with subcutaneous BCG.…”
Section: Introductionmentioning
confidence: 56%
“…In order to confirm the relevance of these mechanisms in vivo, a group of C57BL/6 mice were vaccinated with a clinically relevant dose of MTBVAC [8,28,29] or BCG subcutaneously. After 4 weeks, these mice were challenged with LPS, and the levels of their proinflammatory cytokines were measured in serum ( Fig 4A).…”
Section: Mtbvac Induces Trained Immunity In Vivomentioning
confidence: 99%
“…The primary target population of MTBVAC are neonates; the secondary target population includes adolescents and adults (as a booster vaccine). A Phase Ia trial in adults showed that MTBVAC is safe and immunogenic [56] and a second Phase Ib in neonates in an endemic country showed that MTBVAC is as safe as BCG and more immunogenic [57]. Dose-defining Phase IIa trials in both target populations started in 2019 with funding support from US NIH in collaboration with IAVI in adults (ClinicalTrials.gov NCT02933281) and the EDCTP in collaboration with TBVI in neonates (ClinicalTrials.gov NCT03536117) ( Figure 2).…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%